Phrasematic Introduction to Dialectal Axiolinguistics - Tyrpa, Anna (Vilnius University Open Series, 2021)
The current works related to analysing value in Polish dialects have been presented in the article. The author has selected six types of values. For each of them, two opposite values in the form of adjectives have been chosen. The author has shown how these values are expressed by dialectal phrasemes. Cognitive values: wise (e. g. mądry jak Salomon [as wise as Solomon]) – stupid (e. g. głupi jak motyka [as stupid as a hoe]). Moral values: good (e. g. dobry jak lato [as good as summer]) – evil (e. g. zły jak czart [as bad as the devil]). Vital values: healthy (e. g. zdrowy jak dzwon [as healthy as a bell]) – ill (e. g. chory na śmierć [ill with death]). Values of feelings: satiated (e. g. wiatrem syt [satiated with wind]) – hungry (e. g. głodny jak Żydowa kobyła [as hungry as a Jew’s horse]). Aesthetic values: beautiful (e. g. piękny jak z obrazka [as beautiful as from a picture]) – ugly (e. g. brzydki jak papuga [as ugly as a parrot]). Economic values: rich (e. g. bogaty jak patyk w lesie [as rich as a stick in the forest]) – poor (e. g. biedny jak mysz [as poor as a mouse]).